Formal Methods for Safety and Security Case Studies for Aerospace Applications - Nanda, Manju; Jeppu, Yogananda (Springer Nature Singapore : Imprint: Springer, 2018)
This volume is the outcome of deliberations on formal methods in aerospace. The book specially delves into use of formal methods for verification, validation, and optimization of software in safety critical and time critical applications, such as aerospace. The chapters in this book are authored by leading corporate and government R&D scientists. The contents of this book will be useful to researchers and professionals alike. .